Efektivitas Platform Digital Interaktif dalam Meningkatkan Hasil Akademis: Tinjauan Pustaka Sistematis - Rahayu, Dina (el-Khuwailid: Journal of Multidisciplinary Studies, 2025)
The integration of interactive digital platforms in educational settings has become increasingly crucial for enhancing academic outcomes, yet significant challenges remain in educator technology adaptation. This study examines the effectiveness of interactive digital platforms such as Kahoot and Padlet in improving student academic performance through comprehensive literature analysis. The research identifies critical gaps in previous studies that primarily focused on platform features rather than actual learning outcomes and educator adaptation processes. Using systematic literature review methodology, this study analyzes 45 peer-reviewed articles published between 2019-2024, examining the relationship between platform interactivity, educator technology mastery, and measurable academic improvements. Data analysis employed thematic coding to identify patterns in successful digital learning implementation. Key findings reveal that interactive platforms can increase academic performance by 15-25% when educators demonstrate adequate technology proficiency, but success rates drop significantly when proper training is absent. The study proposes a comprehensive framework integrating platform effectiveness metrics with educator development strategies. Recommendations include structured technology training programs for educators and standardized assessment protocols for measuring digital learning effectiveness.